2019
DOI: 10.1177/1040638719847510
|View full text |Cite
|
Sign up to set email alerts
|

Infection of eight mesocarnivores in New Hampshire and Vermont with a distinct clade of canine distemper virus in 2016–2017

Abstract: Three fishers ( Martes pennanti), 2 gray foxes ( Urocyon cinereoargenteus), 1 mink ( Neovison vison), 1 skunk ( Mephitis mephitis), and 1 raccoon ( Procyon lotor), from Vermont and New Hampshire, had lesions on autopsy consistent with canine distemper virus (CDV) infections diagnosed in a 12-mo period in 2016–2017. Lesions of CDV infection were most commonly noted in the lungs (8 of 8 animals), urothelium (5 of 8), biliary tract (5 of 8), gastrointestinal tract (4 of 7), and brain (4 of 6). Splenic lesions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
(45 reference statements)
1
13
0
Order By: Relevance
“…Numerous CDV strains have been identified in North American wildlife [ 32 ]. The strain detected in this case belongs to a distinct clade that has been reported in 8 carnivores in the Northeast United States in 2016–2017 [ 3 ]. This clade is distinct both from CDV strains used in commercial vaccines, and from others noted in wildlife in the United States [ 3 , 32 ].…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Numerous CDV strains have been identified in North American wildlife [ 32 ]. The strain detected in this case belongs to a distinct clade that has been reported in 8 carnivores in the Northeast United States in 2016–2017 [ 3 ]. This clade is distinct both from CDV strains used in commercial vaccines, and from others noted in wildlife in the United States [ 3 , 32 ].…”
Section: Discussionmentioning
confidence: 74%
“…The strain detected in this case belongs to a distinct clade that has been reported in 8 carnivores in the Northeast United States in 2016–2017 [ 3 ]. This clade is distinct both from CDV strains used in commercial vaccines, and from others noted in wildlife in the United States [ 3 , 32 ]. The two CDV isolates from the foxes we reported herein are most closely related to each other and three isolates from raccoons from Rhode Island, USA.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Mutation in the gene at position 549, with substitution of tyrosine for histidine (Y549H), has been implicated in increased infectivity of non-canid species, particularly felids [ 5 , 6 ] while other studies have shown no bias at this site [ 1 , 7 ]. Epidemiologic investigations of wildlife cases have identified numerous strains and distinct CDV lineages in circulation in domestic and free-ranging carnivore populations [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%